One-dimensional Fermi accelerator model with moving wall described by a nonlinear van der Pol oscillator - Botari, Tiago [UNESP]; Leonel, Edson D. [UNESP] (American Physical Society (APS), 2013)
A modification of the one-dimensional Fermi accelerator model is considered in this work. The dynamics of a classical particle of mass m, confined to bounce elastically between two rigid walls where one is described by a nonlinear van der Pol type oscillator while the other one is fixed, working as a reinjection mechanism of the particle for a next collision, is carefully made by the use of a two-dimensional nonlinear mapping. Two cases are considered: (i) the situation where the particle has mass negligible as compared to the mass of the moving wall and does not affect the motion of it; and (ii) the case where collisions of the particle do affect the movement of the moving wall. For case (i) the phase space is of mixed type leading us to observe a scaling of the average velocity as a function of the parameter (χ) controlling the nonlinearity of the moving wall. For large χ, a diffusion on the velocity is observed leading to the conclusion that Fermi acceleration is taking place. On the other hand, for case (ii), the motion of the moving wall is affected by collisions with the particle. However, due to the properties of the van der Pol oscillator, the moving wall relaxes again to a limit cycle. Such kind of motion absorbs part of the energy of the particle leading to a suppression of the unlimited energy gain as observed in case (i). The phase space shows a set of attractors of different periods whose basin of attraction has a complicated organization. © 2013 American Physical Society.
Keywords: Average velocity; Basin of attraction; Classical particle; Energy gain; Fermi acceleration; Limit cycle; Mixed type; Nonlinear mappings; Phase spaces; Reinjection; Rigid wall; Van der Pol; Van der Pol oscillator; Lyapunov methods; Oscillators (mechanical); Phase space methods; Circuit oscillations